Ecstasy abuse and its effects on the oral mucosa - Biancardi, Mariel Ruivo [UNESP]; Da Silveira, Heitor Albergoni [UNESP]; Fernandes, Darcy [UNESP]; De Almeida, Luciana Yamamoto; Ortega, Rose Mara; León, Jorge Esquiche; Bufalino, Andreia [UNESP] (Wolters Kluwer, 2019)
Ecstasy is an illicit drug that has been increasingly abused by young people. This synthetic drug has both stimulant and hallucinogenic effects and is usually consumed in a tablet. The side effects of ecstasy use include nausea, muscle cramping, fever, and symptoms mostly linked to muscular tension including jaw pain, facial pain, and headaches. There are few studies assessing the ecstasy effects on the oral mucosa, both clinically and histopatho-logically. The authors report 2 young women (22- and 27-year-old) who presented multifocal oral erosions and ulcerations. The lesions were painful and covered by a yellow-white pseudomembrane with a bright erythematous halo. By microscopy, it was observed superficial ulceration surrounded by acanthotic squamous epithelium with marked spongiosis, interstitial edema within the corion and perivascular lyphoid infiltrate, suggesting drug-induced oral mucositis. In conclusion, ecstasy use may be associated with the development of oral ulcers, which should be considered in the differential diagnosis when assessing multifocal oral ulcerations, especially in young people.
Keywords: Drug abuse; Ecstasy; Histopathology; Oral ulcerations